(untitled) (Islamika : Jurnal Ilmu-Ilmu Keislaman, 2022)
Islamic man is the basic assumption of Monzer khaf in his thinking, socio economic justice in Islamic can be achieved when it can combine zakat or alms to the economic aggregate, carry out economic activities in accordance with the rules of Islamic economics, in Islamic consumption, it is required to consume al- Tayyibat and al-Rizq, zakat is ameans of distributing wealh from the rich to the poor, al-Qirad as a form of cooperation between capital owners and entrepreneurs. This money should not be used as a benchmark for prices where the quantity affects various transactions. Therefore, Monzer Khaf is very concerned about the consumption of goods so that there will be no mistakes. Islamic man is the basic assumption of Monzer khaf in his thinking, socio economic justice in Islamic can be achieved when it can combine zakat or alms to the economic aggregate, carry out economic activities in accordance with the rules of Islamic economics, in Islamic consumption, it is required to consume al- Tayyibat and al-Rizq, zakat is ameans of distributing wealh from the rich to the poor, al-Qirad as a form of cooperation between capital owners and entrepreneurs. This money should not be used as a benchmark for prices where the quantity affects various transactions. Therefore, Monzer Khaf is very concerned about the consumption of goods so that there will be no mistakes.